A Contemporary Comparison of Tradition and Postmodernity: The Legitimacy of Astronomical Calculations in Determining the Beginning of Ramadan - Rohile Mohammed Gharaibeh (MILRev: Metro Islamic Law Review, 2026)
The determination of the beginning of Ramadan remains one of the most debated issues in contemporary Islamic legal discourse, particularly regarding the legitimacy of astronomical calculations (hisāb) as an independent method for establishing the commencement of fasting obligations. While classical juristic traditions predominantly emphasized physical crescent sighting (Ru’yah) as the basis for confirming the lunar month, advances in modern astronomy have generated renewed discussions concerning the epistemological status of scientific certainty in Islamic legal reasoning. This study aims to examine the legitimacy of astronomical calculations in determining the beginning of Ramadan through a comparative analysis of traditional and postmodern perspectives on religious authority, knowledge production, and legal interpretation. Employing a qualitative doctrinal methodology, the research analyzes relevant Qur’anic verses, Prophetic traditions, classical and contemporary juristic opinions, and contemporary astronomical findings concerning lunar conjunction and crescent formation. The study adopts a comparative Islamic jurisprudential approach to evaluate the relationship between scriptural interpretation and scientifically verifiable knowledge. The findings reveal that contemporary astronomical calculations have achieved a high degree of precision, enabling accurate determination of the lunar month's commencement without requiring actual naked-eye crescent sighting. Furthermore, the study demonstrates that Prophetic directives concerning crescent observation were closely linked to the empirical capacities of the early Muslim community rather than constituting an exclusive and immutable legal requirement. From a postmodern perspective, the legitimacy of knowledge is no longer confined to a single epistemological authority but may incorporate scientifically validated methodologies that fulfill the objectives of Islamic law. This research contributes to contemporary Islamic legal scholarship by proposing a reconciliatory framework that integrates classical jurisprudential principles with modern astronomical science, thereby offering a constructive approach to reducing recurring disputes over the beginning and end of Ramadan across Muslim communities and nation-states.